Factors Associeted with Home Accidents in Childhood at Regional Teaching Hospital of Ouémé Plateau - ZOHOUN GUIDIBI, LUTECIA MYRIAME (My University, 2022)
Introduction: Home accidents (HA) are often unknown in Benin compared to infectious pathologies. The aim of this work was to determine the prevalence and the factors associated with HA in children admitted to the CHUD-OP. Method: This was a cross-sectional study conducted from August 1st to October 31th 2021. We studied children aged 0 to 18 who presented with HA to the pediatrics and emergency reception and triage departments at CHUD-OP. We defined HA as “any event occurring inside the home or in the immediate vicinity of the home that resulted in an injury which was not done deliberately. Results: The hospital frequency of HA was 8.4% (61/725). The median age was 5 years with a male to female ratio of 1.6. Trauma was the leading cause of HA (59%) followed by poisoning (23%). Falling was the main mechanism of trauma (80.6%). The toxins causing poisoning were dominated by caustics (28.6%). The age of the children (p = 0.02), the level of education of the mothers (p < 0.03), and the area they occur (kitchen with p = 0.04 and on the stairs with p = 0.03) were statistically associated with the occurrence of trauma. Conclusion: HA are common among children admitted at CHUD-OP and factors associated with HA are identified. Measures to prevent home accidents among children in the community should be cons
Keywords: Caustic Soda Poisoning; Home Accidents; Unintentional Home Accidents; Trauma at Home; Associated Factors